A new three-dimensional seismic assessment method (3D-SAM) for buildings based on experimental modal analysis. (February 2017) - Mirshafiei, Farshad; Mirshafiei, Mehrdad; McClure, Ghyslaine
Abstract: Current detailed seismic evaluation methods are based on numerical approaches. However, there is a need to improve the reliability of such evaluations especially in many situations where detailed design documentation is not available. This paper introduces a novel approach for seismic assessment of buildings, 3D-SAM, based on in-field ambient vibration measurements using acceleration/velocity sensors located on building platforms. The proposed method can be used to assess most of building types as it incorporates torsional effects and it does not need the creation of any finite element model. Applications to four buildings located in Montreal are presented that illustrate and validate the proposed method. The results confirm 3D-SAM as a reliable seismic assessment tool for most buildings that would sustain slight damage in an earthquake. The authors have extended the applications to structures that suffer more sever damage in the modified 3D-SAM method which is published in a separate article.